Analisis Fundamental Makro, Struktur Kepemilikan, Profitabilitas Terhadap Nilai Perusahaan dengan Opini Auditor Sebagai Variabel Moderating Objeknya (Studi Kasus Sub: Sektor Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2023) - Calosa, Kristiana Greta; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
In this study, the authors used auditor opinion as a moderating variable to test the effect of macro fundamentals, ownership structure and profitability on firm value. The findings tell us that macro fundamentals work positively and significantly on profitability but have no effect on firm value. Auditor opinion has no significant effect on the value of a company. Ownership structure has no significant effect on the value of a firm as well as profitability. Auditor opinion has no moderating effect on the relationship between macro fundamentals, ownership structure, profitability and firm value. This study provides insight into the relationship between these variables and their impact on firm valuation.